Effects of reported beta‐lactam allergies on pneumonia outcomes in lung transplant recipients. Issue 5 (18th October 2022) - Motzer, Andrew R.; Holaday, Eric; Axelrod, Peter; Mishkin, Aaron
Abstract: Background: The effects of reported beta‐lactam allergies on clinical outcomes have been understudied in lung transplant recipients. We evaluated reported beta‐lactam allergies on clinical outcomes in this population. Methods: A single‐center retrospective cohort analysis was performed. One hundred and nine lung transplant recipients were identified and screened for a diagnosis of pneumonia. This cohort was divided into those with a reported beta‐lactam allergy and those without a beta‐lactam allergy. Antibiotic use was compared between groups. We also compared several clinical metrics, including rates of readmission, mortality, Clostridium difficile infection (CDI), allograft dysfunction, and isolation of carbapenem or fluoroquinolone non‐susceptible organisms after treatment. Results: Of the 109 lung transplant recipients, 18 (16.5%) were identified as having a reported beta‐lactam allergy. Patients with a beta‐lactam allergy label (BLAL) were found to have decreased utilization of beta‐lactams ( p  < .001) and a trend toward increased use of carbapenems ( p = .062) and aztreonam ( p = .080). BLAL patients were found to have higher rates of CDI ( p = .049) but were not found to have increased readmissions, mortality, allograft dysfunction, or isolation of carbapenem or fluoroquinolone non‐susceptible organisms. Patients without a BLAL were found to have higher rates of acute kidney injury (AKI) ( p = .035). Conclusions: Lung transplant recipients with BLAL are more likely to develop CDI, possibly due to increased use of carbapenems. We also found that patients without beta‐lactam allergy were more likely to develop AKI. A multicenter study with a larger sample size might clarify the individual contributions of mutually confounding clinical parameters.